THE INFLUENCE OF GREEN MARKETING AND BRAND IMAGE ON PURCHASE DECISION AT STARBUCKS COFFEE MANADO - Stevania Mokorimban; Marjam Mangantar; Maria V. J. Tielung (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
The purpose of this study was to determine the influence of Green Marketing and Brand Image on Purchase Decision. The variables in this study consist of Green Marketing (X1), Brand Image (X2), and Purchase Decision (Y). This research data is primary data, obtained from the results of the questionnaire distribution design. This study used 100 respondents. Instrument test using Validity Test and Reliability Test using SPSS. Analysis Techniques, Multiple Linear Regression, Classical Assumption Test, F Test and t Test. The results showed that Green Marketing has no significant effect on Purchase Decision, while Brand Image has a positive and significant effect on Purchase Decision. And simultaneously Green Marketing and Brand Image influence Purchasing Decisions.   Keyword: green marketing, brand image, purchase decision